Validação da intradermoreação de Montenegro para diagnóstico de leishmaniose em felinos - Sobrinho, Ludmila Silva Vicente [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Leishmaniasis are protozoan zoonotic diseases transmitted in the Americas by female sandflies of the genus Lutzomyia infected by Leishmania infantum chagasi during blood feeding. Although dogs are well established as the main reservoirs for the disease in urban areas, various reports of cats naturally infected worldwide may indicate an important role of this species in the disease cycle. Since the detection of circulating antibodies in infected cats is difficult, and infected cats in endemic areas are reportedly less likely to develop clinical signs when compared to dogs, this study aimed to evaluate cats living in endemic area by means of parasitological and serological (ELISA and IFAT), real time PCR and Montenegro skin test (MST), in order to use the later test to identify infected cats that did not develop antibody titers or clinical signs of the disease. For this purpose, 96 adult cats, regardless of sex, symptomatic or asymptomatic, from Araçatuba, São Paulo, were evaluated. Considering the results of qPCR and/or parasitological examination, the prevalence of infection in the evaluated population was 55.21% (53/96). Of the infected cats, 58.49% (31/53) were asymptomatic, 62.26% (33/53) females and 41.51% (22/53) aged between 1 and 3 years (p = 0.0002). Most of the infected cats had low antibody titers (37/53, 69.81%) and showed no clinical alterations (24/37, 64.86%). Only two (2.08%) were seroreactive by IFAT with titers of antibodies equal to 1:40. All 96 cats showed negative to MST with leishmanin of L. infantum chagasi (4.107 parasites/mL). Of these, 11 cats were selected and just one was positive to MST with leishmanin of L. (L.) amazonensis (107 parasites/mL). These findings indicate that qPCR demonstrated efficacy and should be used for visceral leishmaniasis diagnosis in cats and the MST, in the conditions in which it was tested, does not constitute a tool for identifying cats infected by L. infantum chagasi
Keywords: Antigenos; Reação em cadeia da polimerase; Imunidade celular; Alergia; Gato; Leishmaniose; Humoral immunity